Effects of arm‐splint rigidity on self‐injury and adaptive behavior. Issue 4 (15th September 2015) - DeRosa, Nicole M.; Roane, Henry S.; Wilson, Jessie L.; Novak, Matthew D.; Silkowski, Erica L.
Abstract : The current study replicated and extended previous research on the use of a rapid assessment to identify effective arm‐splint rigidity with 2 participants who had been diagnosed with autism and who engaged in self‐injurious behavior (SIB). We varied rigidity levels within a multielement design across several adaptive tasks and identified the most effective rigidity level in terms of reductions in SIB and levels of compliance.